Schaum's outline of theory and problem of general topology - Lipschutz, Seymour; Lipschutz, Seymour (Singagore, McGraw Hill Book Company, 1965)
Now an essential part of the mathematical background for both graduate and undergraduate students, general topology, or point set topology, is explained here clearly and concisely. Definitions, principles and theorems are illustrated and reinforced with hundreds of problems with detailed solutions. Hundreds of additional problems with answers help students guage their mastery as they progress. An appendix provides quick access to the basic principles of real numbers, making this a handy reference, too. Table of Content: Sets and Relations Functions Cardinality, Order Topology of the Line and Plane Topological Spaces Definitions Bases and Subbases Continuity and Topological Equivalence Metric and Normed Spaces Countability Separation Axioms Compactness Product Spaces Connectedness Complete Metric Spaces Function Spaces Appendix Properties of the Real Numbers
Appendix 225-234p.; Index 235-239p.
Keywords: Metric; Sets